Mesenchymal Stem Cells Beyond Regenerative Medicine - Shammaa, Riam; El-Kadiry, Abed El-Hakim; Abusarah, Jamilah; Rafei, Moutih (Frontiers in Cell and Developmental Biology, 2020)
Mesenchymal stem cells (MSCs) are competent suitors of cellular therapy due to their therapeutic impact on tissue degeneration and immune-based pathologies. Additionally, their homing and immunomodulatory properties can be exploited in cancer malignancies to transport pharmacological entities, produce anti-neoplastic agents, or induce anti-tumor immunity. Herein, we create a portfolio for MSC properties, showcasing their distinct multiple therapeutic utilities and successes/challenges thereof in both animal studies and clinical trials. We further highlight the promising potential of MSCs not only in cancer management but also in instigating tumor-specific immunity - i.e. cancer vaccination. Finally, we reflect on the possible reasons impeding the clinical advancement of MSC-based cancer vaccines to assist in contriving novel methodologies from which a therapeutic milestone might emanate.